Lutzomyia longipalpis Saliva Induces Heme Oxygenase-1 Expression at Bite Sites - Luz, Nívea Farias (2018)
Fundação de Amparo a Pesquisa do Estado da Bahia (FAPESB) e Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), and by the Intramural Research Program of the NIH, National Institute of Allergy and Infectious Diseases. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001. NL is a fellowship recipient from CAPES Brazil; PM is a fellowship recipient from FAPESB; AV is a fellowship recipient from Programa Nacional de Pós-Doutorado/CAPES; CdO, UL, CB and VMB are senior investigators of CNPq.